2014
DOI: 10.1136/emermed-2014-204260
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with bilateral fixed dilated pupils secondary to traumatic extradural or subdural haematoma who undergo surgery: a systematic review and meta-analysis

Abstract: CRD42013005198.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 25 publications
(16 reference statements)
2
13
0
Order By: Relevance
“…It is a well-established fact that AEDH is more likely to occur in isolation, while ASDH is more likely to be associated with brain parenchyma injury. It is the associated injuries in ASDH that account for the worse prognosis that is documented almost universally [24,25,28]. This assertion is supported by the finding of our study that the difference in average post resuscitation GCS of the two hematoma (12 vs. 10 for AEDH and ASDH, respectively) was statistically significant (p < 0.01).…”
Section: Short-term Treatment Outcome For Intracranial Extra-axial Hesupporting
confidence: 82%
“…It is a well-established fact that AEDH is more likely to occur in isolation, while ASDH is more likely to be associated with brain parenchyma injury. It is the associated injuries in ASDH that account for the worse prognosis that is documented almost universally [24,25,28]. This assertion is supported by the finding of our study that the difference in average post resuscitation GCS of the two hematoma (12 vs. 10 for AEDH and ASDH, respectively) was statistically significant (p < 0.01).…”
Section: Short-term Treatment Outcome For Intracranial Extra-axial Hesupporting
confidence: 82%
“…4 In a systematic review of studies on traumatic SDHs and EDHs with bilateral fixed and dilated pupils, despite the high mortality and morbidity, better functional recovery could be achieved in addition to higher survival rates by aggressive timely surgical interventions. 5…”
mentioning
confidence: 99%
“…Scotter et al investigated the prognosis of patients with bilateral fixed dilated pupils (BFDPs) secondary to an extra-axial haemorrhage who underwent decompressive surgery and published their findings in 2015 2. They concluded that a low threshold for decompression in patients with BFDP and extradural haemorrhages should be adopted, noting that almost two-thirds of patients with extradural haematomas survived after decompression with over half having a good outcome.…”
Section: Discussionmentioning
confidence: 99%